English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

We are trying to find a, b, c, d such that:

(az+b)(cz+d) = 10z^2+11z-6
(az+b)(cz+d) = (ac)z^2+(ad+bc)z-(bd)

Thus, ac=10; ad+bc=11; bd=6

Experimenting with factorizations of 10 and 6, produce a=2; b=3; c=5; d=-2. Thus we get:

(2z+3)(5z-2)

2007-05-02 13:29:08 · answer #1 · answered by NSurveyor 4 · 1 0

10z^2+11z-6
(5z-2)(2z+3)

2007-05-02 13:31:06 · answer #2 · answered by yupchagee 7 · 1 0

(2z + 3)(5z - 2)

2007-05-02 13:29:38 · answer #3 · answered by TychaBrahe 7 · 1 0

(5z-2)(2z+3)

2007-05-07 10:00:42 · answer #4 · answered by Anonymous · 0 0

(2z+3)(5z-2)

2007-05-02 13:35:34 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers